A Balance between B Cell Receptor and Inhibitory Receptor Signaling Controls Plasma Cell Differentiation by Maintaining Optimal Ets1 Levels - Luo, Wei; Mayeux, Jessica; Gutierrez, Toni; Russell, Lisa; Getahun, Andrew; Müller, Jennifer; Tedder, Thomas; Parnes, Jane; Rickert, Robert; Nitschke, Lars; Cambier, John; Satterthwaite, Anne B.; et al. (Journal of Immunology, 2014)
Signaling through the BCR can drive B cell activation and contribute to B cell differentiation into Ab-secreting plasma cells. The positive BCR signal is counterbalanced by a number of membrane-localized inhibitory receptors that limit B cell activation and plasma cell differentiation. Deficiencies in these negative signaling pathways may cause autoantibody generation and autoimmune disease in both animal models and human patients. We have previously shown that the transcription factor Ets1 can restrain B cell differentiation into plasma cells. In this study, we tested the roles of the BCR and inhibitory receptors in controlling the expression of Ets1 in mouse B cells. We found that Ets1 is downregulated in B cells by BCR or TLR signaling through a pathway dependent on PI3K, Btk, IKK2, and JNK. Deficiencies in inhibitory pathways, such as a loss of the tyrosine kinase Lyn, the phosphatase Src homology region 2 domain-containing phosphatase 1 (SHP1) or membrane receptors CD22 and/or Siglec-G, result in enhanced BCR signaling and decreased Ets1 expression. Restoring Ets1 expression in Lyn- or SHP1-deficient B cells inhibits their enhanced plasma cell differentiation. Our findings indicate that downregulation of Ets1 occurs in response to B cell activation via either BCR or TLR signaling, thereby allowing B cell differentiation and that the maintenance of Ets1 expression is an important function of the inhibitory Lyn -> CD22/SiglecG -> SHP1 pathway in B cells.

A balance between BCR and inhibitory receptor signaling controls plasma cell differentiation by maintaining optimal Ets1 levels - Luo, Wei; Mayeux, Jessica; Gutierrez, Toni; Getahun, Andy; Müller, Jennifer; Tedder, Thomas; Chen, Shu-Hsia; Rickert, Robert; Nitschke, Lars; Cambier, John; Satterthwaite, Anne; Garrett-Sinha, Lee Ann (Journal of Immunology, 2014)

Nanoscale organization and dynamics of the siglec CD22 cooperate with the cytoskeleton in restraining BCR signalling - Gasparrini, Francesca; Feest, Christoph; Bruckbauer, Andreas; Mattila, Pieta K.; Müller, Jennifer; Nitschke, Lars; Bray, Dennis; Batista, Facundo D. (EMBO Journal, 2016)
Receptor organization and dynamics at the cell membrane are important factors of signal transduction regulation. Using super-resolution microscopy and single-particle tracking, we show how the negative coreceptor CD22 works with the cortical cytoskeleton in restraining BCR signalling. In naive B cells, we found endogenous CD22 to be highly mobile and organized into nanodomains. The landscape of CD22 and its lateral diffusion were perturbed either in the absence of CD45 or when the CD22 lectin domain was mutated. To understand how a relatively low number of CD22 molecules can keep BCR signalling in check, we generated Brownian dynamic simulations and supported them with exvivo experiments. This combined approach suggests that the inhibitory function of CD22 is influenced by its nanoscale organization and is ensured by its fast diffusion enabling a "global BCR surveillance" at the plasma membrane.
Keywords: B-cell receptor signalling; glycoprotein CD45; membrane dynamics; siglec CD22; super-resolution microscopy

Siglec-G Deficiency Leads to Autoimmunity in Aging C57BL/6 Mice. - Müller, Jennifer; Lunz, Benjamin; Schwab, Inessa; Acs, Andreas; Nimmerjahn, Falk; Daniel, Christoph; Nitschke, Lars (Journal of Immunology, 2015)
Siglec-G, a member of the sialic acid-binding Ig-like lectin (Siglec) family, is expressed on B cell and dendritic cell surfaces. It acts as an inhibitory coreceptor and modulates B cell activation, especially on B1 cells, as Siglec-G-deficient mice show mainly a B1 cell-restricted phenotype resulting in increased B1 cell numbers. Although higher B1 cell numbers are discussed to be associated with autoimmunity, loss of Siglec-G does not result in autoimmune disease in BALB/c mice. However, there is evidence from Siglec-G × CD22 double-deficient mice and Siglec-G(-/-) mice on an autoimmune-prone MRL/lpr background that Siglec-G is important to maintain tolerance in B cells. In this study, we analyzed the role of Siglec-G in induction and maintenance of B cell tolerance on C57BL/6 background and in the FcγRIIb-deficient background. We find that aging Siglec-G-deficient and Siglec-G × FcγRIIb double-deficient mice develop an autoimmune phenotype with elevated autoantibody levels and mild glomerulonephritis. Aging Siglec-G-deficient mice have elevated numbers of plasma cells and germinal center B cells, as well as a higher number of activated CD4 T cells, which likely all contribute to autoantibody production. Additional loss of the inhibitory receptor FcγRIIb in Siglec-G(-/-) mice does not result in exacerbation of disease. These results indicate that Siglec-G is important to maintain tolerance in B cells and prevent autoimmunity.